Abnormal Elevation of Anti-Mullerian Hormone and Androgen Levels Presenting as Granulosa Cell Tumor - Chi, Hongbin; Huang, Ning; Liang, Huamao; Li, Rong; Liu, Congrong; Qiao, Jie (Frontiers in Oncology, 2021)
We report a rare subtype of adult cystic granulosa cell tumor (AGCT) characterized by elevated anti-Mullerian hormone and hyperandrogenism. A 35-year-old woman with primary infertility, hyperandrogenism, and irregular menses who was previously misdiagnosed with polycystic ovarian syndrome was diagnosed with AGCT based on histopathological examination and FOXL2 genetic test after laparoscopy. Due to fertility aspirations, she underwent controlled ovarian stimulation followed by embryo cryopreservation before salpingo-oophorectomy, and two embryos were frozen-thawed and transferred after surgery. A healthy female infant was delivered at 40 weeks’ gestation. Cystic granulosa cell tumors should be considered a differential diagnosis in patients with persistent ovarian cysts and hyperandrogenism. Younger patients with AGCT with fertility goals should consider active assisted reproduction measures to preserve fertility before treatment for AGCT.